2018
DOI: 10.1111/acem.13442
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pulmonary Embolism Risk Classification and Guideline Adherence for Computed Tomography Pulmonary Angiography Ordering

Abstract: The Wells and revised Geneva score risk classifications can be approximated with high accuracy using automated extraction of structured EHR data elements in patients who received a CTPA. Combining these automated scores with D-dimer ordering data allows for the automated assessment of clinical guideline adherence for CTPA ordering in the ED, without the burden of manual chart review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…At our institution, although users of a CDS tool incorporating the Wells score had CTPA yields of 38% higher than nonusers, the tool was dismissed in 65% of the cases [13]. Rather than requiring burdensome review of fragmented clinical data [14][15][16] and manual input of score components by providers, a CDS tool that presents a Wells score automatically calculated from existing EHR data could improve efficiency and usability and thereby tool acceptance [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…At our institution, although users of a CDS tool incorporating the Wells score had CTPA yields of 38% higher than nonusers, the tool was dismissed in 65% of the cases [13]. Rather than requiring burdensome review of fragmented clinical data [14][15][16] and manual input of score components by providers, a CDS tool that presents a Wells score automatically calculated from existing EHR data could improve efficiency and usability and thereby tool acceptance [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…At our institution, although users of a CDS tool incorporating the Wells score had CTPA yields of 38% higher than nonusers, the tool was dismissed in 65% of the cases [ 13 ]. Rather than requiring burdensome review of fragmented clinical data [ 14 - 16 ] and manual input of score components by providers, a CDS tool that presents a Wells score automatically calculated from existing EHR data could improve efficiency and usability and thereby tool acceptance [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis of the Wells score concluded that it is less amenable to automatic calculation due to the inclusion of variables that either require clinical gestalt (PE as or more likely than alternative diagnosis) or are likely to be embedded in unstructured data (clinical signs and symptoms of deep venous thrombosis [DVT] and hemoptysis) [ 19 ]. Yet, using narrow definitions of the Wells score components based only on structured data can lead to decreased sensitivity for relevant clinical documentation [ 17 ]. The objective of our study was to design an automated process that incorporates information from unstructured data, and to validate its accuracy.…”
Section: Introductionmentioning
confidence: 99%